A taste for life : how the Spur legend was born - Ambor, Allen (Cape Town, South Africa : Tafelberg, an imprint of NB Publishers, 2021)
"Join Allen Ambor on a rock 'n' roll ride through SA's restaurant business. His exuberance for life and exacting management style shine through in this memoir of a man who went from opening the first Spur in 1967 to growing it into an empire that included more than 500 franchises under the Spur, Panarottis, John Dory's and RocoMamas brands."
Keywords: Ambor, Allen; Spur Steak Ranches; Restaurateurs -- South Africa -- Biography; Restaurant management -- South Africa; Franchises (Retail trade) -- South Africa